Prevalence of thrombocytopenia in children with dengue fever in a tertiary care hospital - Kunwar, Subarna; Devkota, Askal; Shrestha, Prapti; Regmi, Amuda; Shrestha, Mridusha; Chaudhary, Roshan (Grande Medical Journal, 2025)
Background Dengue fever is an arthropod borne viral disease transmitted by bite of infected mosquito Aedes aegypti. Almost half of the world population is in risk of dengue and in Nepal dengue fever is endemic and infection occurs each year in most provinces. Thrombocytopenia is one of the most important complication of dengue fever.This study was aimed to determine the prevalence and severity of thrombocytopenia in children with dengue fever. Method A cross-sectional study was conducted at Nepal Police Hospital by retrospectively reviewing the medical records of children (1 day to 16 years old) diagnosed with dengue fever between April 2023 and April 2025. Data on fever duration, platelet count, dengue serology, and admission status were collected. Ethical approval was obtained, and consecutive sampling was used. Result Out of total 130 cases with dengue fever 27(20.8%) cases had thrombocytopenia. Among 130 cases 73 cases were male and 57 cases were female with gender ratio of 1.2:1. Mean age of presentation was 10.7years (SD ± 4.88). Majority of cases (73.1%) were diagnosed in month of October to December. Among dengue positive cases NS1 antigen was positive in 96.2% cases. Conclusion The prevalence of thrombocytopenia in dengue fever was lower than other studies done in similar setting.